Adhesins of Leptospira interrogans mediate the interaction to fibrinogen and inhibit fibrin clot formation in vitro. - Rosane Oliveira; Renan F Domingos; Gabriela H Siqueira; Luis G Fernandes; Natalie M Souza; Monica L Vieira; Zenaide M de Morais; Silvio A Vasconcellos; Ana L T O Nascimento (Public Library of Science (PLoS), 2013)
We report in this work that Leptospira strains, virulent L. interrogans serovar Copenhageni, attenuated L. interrogans serovar Copenhageni and saprophytic L. biflexa serovar Patoc are capable of binding fibrinogen (Fg). The interaction of leptospires with Fg inhibits thrombin- induced fibrin clot formation that may affect the haemostatic equilibrium. Additionally, we show that plasminogen (PLG)/plasmin (PLA) generation on the surface of Leptospira causes degradation of human Fg. The data suggest that PLA-coated leptospires were capable to employ their proteolytic activity to decrease one substrate of the coagulation cascade. We also present six leptospiral adhesins and PLG- interacting proteins, rLIC12238, Lsa33, Lsa30, OmpL1, rLIC11360 and rLIC11975, as novel Fg-binding proteins. The recombinant proteins interact with Fg in a dose-dependent and saturable fashion when increasing protein concentration was set to react to a fix human Fg concentration. The calculated dissociation equilibrium constants (K D ) of these reactions ranged from 733.3 ± 276.8 to 128 ± 89.9 nM for rLIC12238 and Lsa33, respectively. The interaction of recombinant proteins with human Fg resulted in inhibition of fibrin clot by thrombin-catalyzed reaction, suggesting that these versatile proteins could mediate Fg interaction in Leptospira. Our data reveal for the first time the inhibition of fibrin clot by Leptospira spp. and presents adhesins that could mediate these interactions. Decreasing fibrin clot would cause an imbalance of the coagulation cascade that may facilitate bleeding and help bacteria dissemination.